Transmission electron microscopy of zebrafish spinal motor nerve roots. Issue 11 (28th June 2017) - Morris, Angela D.; Erisir, Alev; Criswell, Stacey J.; Kucenas, Sarah
Abstract : Background : Spinal motor nerves are essential for relaying information between the central and peripheral nervous systems. Perturbations to cell types that comprise these nerves may impair rapid and efficient transmission of action potentials and alter nerve function. Identifying ultrastructural changes resulting from defects to these cellular components via transmission electron microscopy (TEM) can provide valuable insight into nerve function and disease. However, efficiently locating spinal motor nerves in adult zebrafish for TEM is challenging and time‐consuming. Because of this, we developed a protocol that allows us to quickly and precisely locate spinal motor nerve roots in adult zebrafish for TEM processing.Results: Following fixation, a transverse slab of adult zebrafish dissected from the trunk region was mounted in embedding media, sectioned, and secondary fixation with osmium tetroxide performed. Transverse sections containing motor nerves were selected for TEM ultrathin sectioning and imaging.Conclusions: We developed an efficient protocol for locating spinal motor nerves in adult zebrafish to allow for ultrastructural characterization. Although our work focuses on spinal motor nerves, this protocol may be useful for efficiently identifying other discrete, repeated structures within the developing and mature nervous system that are difficult to find via traditional, whole organism TEM processing. Developmental Dynamics 246:956–962, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Rapid and efficient localization of motor nerves in adult zebrafish. Combining antibody labeling with TEM. This protocol can be adapted to rapidly locate other, repeated structures within the adult zebrafish.